Honorifics in Newspapers: The Announcement of Queen Elizabeth Death. A Pragmatic Study - Ruaa Hamdallah , Researcher (lark, 2023)
The significance of words is not based on sensory input but in terms of what that input means when it is perceived. This is the basis of social relationships, and it is the basis that reflects the social knowledge. Politeness is realised through the choice of suitable language expressions according to the situational and social context. Honorific forms are the typical linguistic expressions for exhibiting politeness since their use presumes pragmatic agreement with the situation. Honorifics are a politeness method in a specific language which may be particular words, or sentence structures. The current study aims to find out how the newspapers announced the death of Queen Elizabeth and how they honored her by using different types of honorific expressions. Ten newspapers (five from The United Kingdom and five from The United States of America) have been chosen to be analysed based on Levinson’s (1983) model. According to the findings, most newspapers use referent honorifics and authorised recipient kinds to indicate the nature of the speaker’s regard for the person being referred to.